Responsiveness and minimal clinically important difference of the Brief-BESTest in people with COPD after pulmonary rehabilitation - Paixão, Cátia (2022)
The Brief-Balance Evaluation Systems Test (Brief-BESTest) is a comprehensive, reliable, and valid balance test that provides valuable information to guide balance training in people with chronic obstructive pulmonary disease (COPD). Its clinical interpretability is, however, currently limited, as cutoff points to identify clinically relevant changes in people with COPD after pulmonary rehabilitation are still lacking. This study aimed to establish the responsiveness and minimal clinically important difference (MCID) for the Brief-BESTest in people with COPD after pulmonary rehabilitation (PR).